Understanding the Transdiagnostic Model of Eating Disorders and the Treatment of Perfectionism in Adolescents - Jones, Emily Jane (Curtin University, 2021)
Emily’s PhD investigated factors associated with adolescent mental health. She used a range of research designs to examine how an existing model can be applied to adolescents to understand factors which may be associated with eating disorder symptoms. This included the analysis of cross-sectional and longitudinal data, as well as an intervention. The findings of this research provide insights into factors that are important to consider in the prevention and treatment of adolescent psychological disorders.